The genus Xylaria (Xylariaceae, Ascomycota) in the tropical dry forest from Mexico - Osorio-Navarro, Yulena; Valenzuela , Ricardo; Bautista-Hernández, Silvia; Mendoza-González, A. Catalina; Mateo-Cid, Luz Elena; Raymundo, Tania (Instituto de Ecología, A.C., 2022)
Backgrounds and Aims: The genus Xylaria presents dark perithecial stromas with great morphological variability, cylindrical asci with amyloid apical pore and dark brown ellipsoid ascospores, with or without germ line. It has a worldwide distribution, more than 250 species have been described, with largest diversity in tropical regions. In Mexico, 109 taxa are known, of which 17 have been registered in localities with tropical deciduous forest. The main objective of the present study is to describe the Xylaria species that are found in this type of vegetation and so recognize their distribution. Methods: Specimens from localities with tropical deciduous forest of Mexico and deposited in the fungal collection of the herbarium ENCB were studied. They were examined macro- and micromorphologically following conventional mycological techniques. Key results: Twenty species of the genus Xylaria have been recorded in the deciduous tropical forests of Mexico. Eight of them are described in this work because they are considered less frequent. Xylaria titan is recorded for the first time, from the Chamela-Cuixmala Biosphere Reserve, Jalisco, for Mexico. Xylaria alata, X. apiculata, X. bambooensis, X. claviceps, X. feejeensis, X. grammica, X. laevis, X. longiana, X. multiplex, X. oxyacanthae and X. scruposa are new records for some states. Xylaria apiculata and X. claviceps also are reported for the first time for this type of vegetation in the country. Conclusions: Xylaria is a little represented genus in the tropical deciduous forest of Mexico. The previously known geographical distribution of Xylaria species in tropical deciduous forest is extended. However, in the Neotropical region, ecological, biogeographical and molecular studies are needed for a better understanding of the taxon.